Modulation of microglial phagocytosis via the GAS6-MERTK pathway regulates pathological angiogenesis in the mouse oxygen-induced retinopathy model - Canelif Yilmaz; Irina Korovina; Anke Witt; Farid Abdallah; Bianca Müller; Carmen Hentsche; Anika Fleischhauer; Stephan Speier; Andreas Deussen; Anne Klotzsche - von Ameln (Cell Death and Disease)
Abstract Ischemic retinopathies (IR) are major causes of blindness worldwide. They are characterized by an exuberant hypoxia-driven pathological neovascularization (NV). While it is well accepted that immune cells contribute to both physiological and pathological retinal angiogenesis, our knowledge of various processes and underlying mechanisms, especially in the direct interaction with endothelial cells (EC), is still very limited. Here, we addressed the role of microglial phagocytosis of apoptotic EC in the context of pathological hypoxia-related NV in the mouse oxygen-induced retinopathy model (OIR). We utilized endothelium-specific fluorescent reporter mice to study the kinetics of EC phagocytosis by leukocytes in OIR. Indeed, we observed phagocytic microglia in close proximity to the pathological vessels and an altered phagocytosis rate by flow cytometry compared to controls. We observed a decrease in the phagocytic rate in early hypoxia-driven stages of OIR, whereas in later stages where pathological vessels appear, the phagocytosis rate was increased. Myeloid-specific deletion of the suppressor of cytokine signaling protein 3 (SOCS3) was previously shown to induce increased phagocytic activity due to overexpression of the opsonin molecule growth arrest-specific 6 (GAS6). In myeloid SOCS3-deficient mice, we observed a reduction of pathological NV in OIR. This reduction could be reversed by neutralizing GAS6 via administration of recombinant MERTK protein, the receptor for GAS6 expressed on myeloid cells. Furthermore, exogenous GAS6 supplementation increased microglial phagocytosis in vitro and limited pathological NV in OIR. Our data suggest that the promotion of immune cell phagocytosis by the modulation of the GAS6-MERTK axis might represent a potential target for the treatment of pathological NV in IR.